Legislating cultural organisations under central government: evolution of the public entities organic laws in Portugal - Mendes, Tiago; Costa, P. (81st Annual Midwest Political Science Association Conference, 2024)
BRIEF OVERVIEW: We analyse the legislative reforms that impacted the organisational structure of the entities under supervision of the Ministry of Culture in Portugal, evaluating the causes of this legal evolution and their impact on these organization's autonomy. ABSTRACT: In the context of its autonomization as a political sector, the organizational structure of the entities under central supervision of Culture in Portugal has been reconfigured by multiple legislative reforms, impacting their formal autonomy. The compilation of the legal diplomas (organic laws ) that shaped these organizations in the democratic period, between 1974 and 2022, allows for a longitudinal analysis of this sector's central state administration. This working paper identifies phenomena and trends (organic concentration and deconcentration, prevalence of legal statutes), analyzes the possible causes of their evolution and problematises the implications for the autonomy of the organizations. As relevant agents in the policy implementation, the analysis of these public administration bodies's statutes may impact future reforms and legislative designs, as well as cultural policy as whole.